Health Literacy of Children and Adolescents with Inflammatory Bowel Disease (IBD) and Parents of IBD Patients—Coping and Information Needs - Kaul, Kalina; Schumann, Stefan; Sander, Cornelia; Däbritz, Jan; de Laffolie, Jan; Justus Liebig University Giessen (My University, 2024)
Background: The number of children and adolescents with inflammatory bowel disease (IBD) is increasing. Many chronically ill children and adolescents have low health literacy. Patient empowerment (PE) enables positive changes and control over one’s disease through specific activities, information, and counseling. The CEDNA (IBD Needs Assessment) Survey aimed to provide the necessary data to improve PE in pediatric IBD (PIBD). Methods: Questionnaires were distributed to adolescent IBD patients and parents of children and adolescents with IBD throughout Germany. The answers were given anonymously. Based on the available data, a subgroup analysis was conducted in relation to the age of the patients and the period since diagnosis. For the parents’ responses, the same age groups were analyzed for comparison with the patients’ responses. Results: From October 2021 to April 2022, 2810 questionnaires were distributed and 1158 questionnaires were completed (n = 708 parents [61.1%], n = 450 patients [38.9%]). The results indicate that health literacy in children with IBD is low. Significant gaps in knowledge of important IBD topics were identified, and a comparison of responses regarding preferred methods and timing of obtaining information revealed differences between patient and parent preferences. The greatest need for knowledge on IBD topics was found in the group of 16–17-year-old patients on transition (n = 214, 31.8%) and in the group of patients diagnosed 1–2 years ago on the causes of IBD (n = 288, 17.4%). The willingness to seek advice was unexpectedly low. Conclusions: The analysis of all findings according to the patient’s age structure and duration since diagnosis can be used to enable age-appropriate communication at certain stages of the disease. This tailored information should increase patients’ health literacy, improve their management of the disease, and reduce the burden on their families.
Keywords: ddc:610